AB0883 Denosumab: Patterns of Prescription and Side Effects in 68 Patients. (9th June 2015) - Erra, A.; Grados, D.
Abstract : Background: Denosumab is a human monoclonal antibody (IgG2) that targets and binds with high affinity and specificity to RANKL. It is indicated for the treatment of osteoporosis in postmenopausal women and in men with high risk of fractures. Objectives: To describe the clinical characteristics, indications, side effects and densitometric parameters in patients treated with denosumab. Methods: Retrospective study (2012-2014). We reviewed the medical records of patients treated with denosumab. We collected the epidemiological and clinical features and side effects. Results: Sixty-eight patients received denosumab, all of them women with an average age of 74.8 years (60-91 years). All of them had osteoporosis: postmenopausal in 48 patients (70.5%) and secondary in 20 patients (29.5%): 9 early menopause, 6 primary hyperparathyroidism, 2 glucocorticoid treatment and 2 epilepsy. Fifty-two patients (76.4%) had received other treatments previously (70.5% oral or intravenous bisphosphonates, 16.2% teriparatide or PTH1-84, 19.1% strontium ranelate, 5.9% SERMS). Sixteen patients (23.5%) had no prior treatment performed mostly by gastric intolerance. Forty patients (58.8%) had fractures before treatment: vertebral (29.4%), wrist (17.6%), femur (8.8%) and other (19.1%): pubic rami, sacrum and humerus. The average of bone mineral density before treatment was: T score -3.2 in the lumbar spine (L2-L4) and -2.6 in the femur, and after treatment (36 patients) was: T score -2.6 in the lumbar spine and -2.1 in the femur. Before injecting each dose of denosumab, all patients underwent an analytic with calcium and phosphorus metabolism in which we checked that calcium levels were correct. All patients received calcium supplements and vitamin D. We observed that in the analysis prior to the second dose of denosumab, 14 patients had elevated PTH values (average of 88pg/ml), vitamin D average of 26.8ng/ml, with previous normal values (10-65pg/ml). Out of all patients, 4 had received a single injection, 30 two, 12 three, 12 four, 7 five and 3 six injections of denosumab. Twelve patients suffered side effects (17.6%): urine infections and otitis (3 patients), symptomatic hypocalcemia (3 patients), arthralgia (2 patients), toothache (1 patient), tooth loss (1 patient), leukopenia (1 patient) and abnormal liver tests (1 patient). Two patients (3%) had fractures after treatment: a patient with polio presented a vertebral fracture during a treatment break and a patient who had previously undergone 10 years of oral bisphosphonate presented bilateral femoral shaft fractures. Conclusions: The treatment was well tolerated and only a small percentage of patients was suspended by mild side effects. Densitometric values showed an improvement in both spine and femoral neck. Two fractures were observed during follow-up of patients, one in a patient with spinal polio and bilateral femoral shaft fractures four months after administration of denosumab in a patient previously treated over 10 years with bisphosphonate. Disclosure of Interest: None declared